A new species of the genus Atypus Latreille, 1804 (Araneae: Atypidae) from Korea - Lee, Sue Yeon; Lee, Joon-Ho; Yoo, Jung Sun; Kim, Seung Tae (Zootaxa, 2015)
Worldwide, 30 species of the genus Atypus Latreille, 1804 have been recorded from the United States, Europe, Africa, south-east and far-east Asia (Platnick 2014). Atypid spiders are characterized by a male sternum with marginal ridges, a short, straight and spike-like embolus, a straight conductor and a distally widened vulva with bulbous or pyriform receptacula and with two lateral patches of pores on the genital atrium (Gertsch and Platnick 1980). Kraus and Baur (1974) utilized various taxonomic characters to distinguish between the European species, such as the segmentation of the posterior spinnerets, features of the patellar membrane, morphology of sigilla opposite coxae I and IV, and the male palpal conductor, palpal furrow and male metatarsal spines. The genus Atypus was reviewed by Schwendinger (1990) who redescribed 12 recorded species and discussed the granular texture on the male chelicerae and front legs, and the cymbial pit for distinguishing species. Among 30 Atypus spiders, 18 species are distributed in Far-East Asia; 12 species from China (Zhu et al. 2006), 5 species from Korea (Kim 1985; Namkung 1986, 2001; Kim et al. 2006), and 2 species from Japan (Bösenberg and Strand 1906; Tanikawa 2006).